Multifunctional, Ultra-Flyweight, Synergistically Assembled Carbon Aerogels - Sun, Haiyan; Xu, Zhen; Gao, Chao (Advanced materials (Weinheim), 2013)
All carbon aerogels (up to 1000 cm3) with ultralow density (down to 0.16 mg cm−3) and temperature‐invariant (‐190–900 °C) super‐elasticity are fabricated by facile assembling of commercial carbon nanotubes (CNTs) and chemically‐converted giant graphene sheets, on the basis of the synergistic effect between elastic CNTs ribs and giant graphene cell walls.